2018
DOI: 10.1080/10962247.2017.1367738
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of spent coffee grounds recycling as a potential alternative fuel resource in Turkey: An experimental study

Abstract: Coffee is a huge industry, and coffee has been widely used due to its refreshing properties. This industry generates large quantities of waste. Therefore, recycling of spent coffee grounds for producing alternative fuels and compounds of added value is crucial. Elemental analysis indicated that coffee waste can be utilized as compost, as it is rich in nitrogen. Coffee waste after oil extraction is an ideal feedstock for ethanol and biogas production, garden fertilizer, and as fuel pellets. The low degree of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 33 publications
2
34
0
2
Order By: Relevance
“…For instance, coffee parchment is occasionally processed in thermal facilities to recover energy (ADAMS and GHALY, 2007), while spent coffee grounds have been used as fertilizer, but it was hindered due to its low N content and high acidity (VEGA et al, 2015). Besides, spent coffee grounds have also been used as a fuel due to its high calorific value (ATABANI et al, 2018) or as precursors for activated carbons preparation (REFFAS et al, 2010), biodiesels (KONDAMUDI et al, 2008, or as sorbent materials for heavy metals (KIM et al, 2014).…”
Section: Biochars Characterizationmentioning
confidence: 99%
“…For instance, coffee parchment is occasionally processed in thermal facilities to recover energy (ADAMS and GHALY, 2007), while spent coffee grounds have been used as fertilizer, but it was hindered due to its low N content and high acidity (VEGA et al, 2015). Besides, spent coffee grounds have also been used as a fuel due to its high calorific value (ATABANI et al, 2018) or as precursors for activated carbons preparation (REFFAS et al, 2010), biodiesels (KONDAMUDI et al, 2008, or as sorbent materials for heavy metals (KIM et al, 2014).…”
Section: Biochars Characterizationmentioning
confidence: 99%
“…[37] The observed high level of calorific value CV (MJ·kg −1 ) could be caused by the presence of residual oil in the SCG. As the literature reports, the content of residual oil in SCG occurs at the following levels: 13.0% [38], 14.7% [34], 28.3%. Moreover, the calorific value CV (MJ·kg −1 ) of SCG residual oil occurred at an extremely high level, specifically 36.4 MJ·kg −1 [35].…”
Section: Fuel Parametersmentioning
confidence: 77%
“…If compare results of tested mechanical quality indicators, all of them proved the higher mechanical quality of bio-briquette samples produced from A + B mixtures. First monitored (calculated) indicator, the bulk density ρ (kg·m −3 ), proved a satisfactory level of all produced bio-briquette samples if compared with the requirements for commercial sale; ρ should range between 900-1200 kg·m −3 [37][38][39]. Observed data noted in Table 13 provide a clear comparison between all tested bio-briquette samples, while Table 13 provides a comparison between bulk densities ρ (kg·m −3 ) of bio-briquette fuel produced from different feedstock materials.…”
Section: Mechanical Qualitymentioning
confidence: 99%
“…Since SCG contain a high percentage of carbohydrates, proteins and lipids, they have been investigated as a source of biogas production [38]. Atabani et al [39] suggested a research approach utilizing organic solvent extractives for biodiesel and glycerin production from SCG, while the remaining solids fraction was used as feedstock for ethanol fermentation or biogas production. However, specific attempts to produce biogas were not performed via sequentially exploiting solid fraction remaining after extracting both lignin and lipids by organosolv treatment.…”
Section: Digestibility Of Scg Residues In a Batch Anaerobic Digestermentioning
confidence: 99%